1999
DOI: 10.1097/00003246-199909000-00043
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam coma for refractory status epilepticus in children

Abstract: Midazolam infusion, as per our described algorithm, is effective in terminating refractory status epilepticus. This treatment is not associated with cardiovascular instability, even at doses resulting in burst suppression. In the majority of cases, cessation of seizures occur before burst suppression is achieved on EEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…Numerous clinical studies have shown that midazolam bolus (0.1–0.3 mg/kg) followed by continuous infusion (0.05–2.0 mg/kg/hour) rapidly controls seizures that have not responded to traditional first, second, and even third-line agents [36,37]. Reports of clinically significant hypotension are rare, and sedation is rapidly reversed after infusion is stopped.…”
Section: Treatment Of Refractory Status Epilepticusmentioning
confidence: 99%
“…Numerous clinical studies have shown that midazolam bolus (0.1–0.3 mg/kg) followed by continuous infusion (0.05–2.0 mg/kg/hour) rapidly controls seizures that have not responded to traditional first, second, and even third-line agents [36,37]. Reports of clinically significant hypotension are rare, and sedation is rapidly reversed after infusion is stopped.…”
Section: Treatment Of Refractory Status Epilepticusmentioning
confidence: 99%
“…Table 2 shows the treatments generally accepted as useful, with published case series or case reports. 17,75,78,79,[81][82][83][84][85][86][87][88] There are relative advantages and disadvantages to each of the listed treatments that must be balanced against the gravity of the clinical situation. In nearly all circumstances of refractory status epilepticus, treatment in an intensive care setting is mandatory.…”
Section: Treatment Of Refractory Status Epilepticus In Childrenmentioning
confidence: 99%
“…However, previous studies identified an apparent discrepancy: treatment dosing from studies using EEG monitoring to guide therapy [13,19] used considerably higher doses of midazolam when compared with studies using a clinical endpoint to guide treatment (10.7 mcg/kg/min versus 2.8 mcg/kg/min). [12,1418,20,21] The current pSERG cohort illustrates that an EEG endpoint is currently used in over half of patients and also confirms the utilization of higher midazolam dosing when EEG serves as the endpoint measure (i.e., cessation of EEG seizures 3.8 [2.8 – 5.8] mcg/kg/min or burst suppression 16.7 [9.2 – 25.0] mcg/kg/min).…”
Section: Discussionmentioning
confidence: 99%